Traversing the organizational landscape: personal narrative and the changed self - Marx, Rachel Leone, author; Banning, James H., advisor; Sample, Pat L., advisor; Lehmann, Jean P., committee member; Lewis, Chance W., committee member (Colorado State University. Libraries, 2007)
This research study utilized the methods of autoethnography, a genre of qualitative research that portrays the experiences of the researcher through participant observations, while simultaneously depicting the larger cultural context. The question guiding this research asked, "As an emerging leader within a healthcare organization, what are my experiences initiating a change process and what meanings do I derive from them?" Fullan's (2001) model of leading in a culture of change provided the conceptual framework for this study. His five components of effective leadership were described early on, allowing latter comparison to be made between his model and this researcher's lived experience. While Fullan portrayed five distinct and consecutive components, this researcher's experience depicted a more collaborative approach with less distinction between and different chronological order between components. Additionally, building effective working relationships was evidenced throughout the entire manuscript, rather than Fullan's portrayal of relationships as a separate component. Data were coded and presented as a series of chronological vignettes. The use of personal narrative for this research study was intended to expose the reader and researcher to poignant experiences so that reflections and meaning about the change process may be evoked.
Keywords: school administration; educational administration